IMPROVING STUDENTS' LEARNING OUTCOMES THROUGH OPEN-ENDED PROBLEM MODEL AT GRADE IV SD RK BINTANG TIMUR RANTAUPRAPAT - Tessya Amarki Manihuruk; Patri Janson Silaban; Asnita Hasibuan (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2021)
The results of the study indicated an increase on students’ learning outcomes. The average score at the pretest was 65,76 and the level of the classical completeness was 23%. After implementing Open Ended Problem model in cycle I, the average score of the students’ learning outcomes increased to 69,89 with the level of classical completeness of 33%. Moreover, after the implementation and the posttest conducted in cycle II, it was revealed that 24 students completed their learning outcomes and 6 students did not complete thei learning outcome and the average score of the posttest in cycle II increased to 80,86 with the classical completeness of 80%. This study concluded that Open Ended Problem model improved students’ learning outcomes at grade IV SD RK Bintang Timur Rantauprapat in the Academic Year 2019/2020. Based on the results of the study, the teacher was suggested to implement Open Ended Problem model since it was proven to improve the students’ learning outcomes.